2014
DOI: 10.1097/ans.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Frailty Framework Among Vulnerable Populations

Abstract: Frailty is a significant public health issue which is experienced by homeless and other vulnerable adults; to date, a frailty framework has not been proposed to guide researchers who study this hard-to-reach population. The Frailty Framework among Homeless and other Vulnerable Populations (FFHVP) has been developed from empirical research and consultation with frailty experts in an effort to characterize antecedents, i.e. situational, health-related, behavioral, resource, biological, and environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…These changes could be a product of the increasing awareness of frailty, as healthcare professionals and researchers have been focusing more on this subject over the past several years. In fact, health policy initiatives have been created that focus on postponing/preventing frailty among older adults …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could be a product of the increasing awareness of frailty, as healthcare professionals and researchers have been focusing more on this subject over the past several years. In fact, health policy initiatives have been created that focus on postponing/preventing frailty among older adults …”
Section: Discussionmentioning
confidence: 99%
“…In fact, health policy initiatives have been created that focus on postponing/preventing frailty among older adults. [28][29][30] Regarding the five criteria, exhaustion seems to be the one with the highest weight in frailty assessment for both the 50-64 years and ≥65 years age groups. In the 50-64 years age group, exhaustion (30.7%) was followed by low activity (11.9%), shrinking (6.4%), weakness (6.1%) and slowness (2.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a health state related to ageing, characterised by loss of in-built reserves across multiple body systems and associated with vulnerability to adverse outcomes (Fried et al, 2001;British Geriatrics Society, 2015). Four studies assessed frailty among PEH in the USA using a variety of definitions, finding more than half of participants were frail (Salem et al, 2013(Salem et al, , 2014Hadenfeldt et al, 2017;Salem et al, 2019), and studies in the USA and Ireland reported premature onset of geriatric conditions such as cognitive and functional impairments (Brown et al, 2012(Brown et al, , 2017Ni Cheallaigh and Sears, 2018). In the UK, people living in hostels often have very complex health and social care needs (Shulman et al, 2018;Manthorpe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed study was guided by the frailty framework among vulnerable populations (FFVP) (Salem et al 2014), the Integral Conceptual Model of Frailty (Gobbens et al, 2012), and formative qualitative work with P/FHW (Salem and Ma-Pham 2015) and homeless service providers (HSPs) (Salem et al 2017) which helped us further explore and identify health, social service delivery needs, challenges experienced, and whom should deliver the program. The FFVP depicts individual-level, situational, health-related, and behavioral antecedent variables which contribute to frailty (Salem et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The FFVP depicts individual-level, situational, health-related, and behavioral antecedent variables which contribute to frailty (Salem et al 2014). In particular, individual-level factors (e.g., chronological age, race or ethnicity, marital status, and having children), situational factors (e.g., first time homeless), health-related factors (e.g., back pain, comorbid conditions, depressive symptomology and falls), behavioral factors (e.g., drug and alcohol use), resource factors (e.g., social support) were hypothesized to influence frailty (e.g., physical, psychological and social frailty).…”
Section: Introductionmentioning
confidence: 99%